Human resources management for hospitality - Jerris, Linda A. (Upper Saddle River, NJ : Prentice Hall, 1999)
THis book is about the Human Resources Department, Human Resources Management Challenges, The Legislative Environment, Staffing and the Strategic Huamn Resources Plan...
Keywords: Hospitality industry; Personnel management; Hospitality industry -- Personnel management